Update in Pediatrics (Springer International Publishing, 2018)
This concise and comprehensive volume updates health professionals on recent advances in the field of pediatrics. It includes chapters in every subspecialty of pediatrics, such as critical care, development emergency medicine and genetics. Ranging from traditional disciplines such as infectious disease and cardiology to more current disciplines such as adolescent medicine, metabolics and genetics this is an indispensable guide for the busy clinician who wishes to stay up-to date with latest advances in the field. Through the use of summaries and bullet points, the book conciselly describes the latest recommendations and guidelines in pediatrics and provides a good overview of the available technology for each subspecialty. The team of authors is made up of experienced clinicians and researchers in their respective fields. This book appeals to pediatricians, family doctors, nurses and nurse practitioners, allied health professionals, and health researchers.